2018
DOI: 10.1038/s41467-018-04356-9
|View full text |Cite
|
Sign up to set email alerts
|

Targetable vulnerabilities in T- and NK-cell lymphomas identified through preclinical models

Abstract: T- and NK-cell lymphomas (TCL) are a heterogenous group of lymphoid malignancies with poor prognosis. In contrast to B-cell and myeloid malignancies, there are few preclinical models of TCLs, which has hampered the development of effective therapeutics. Here we establish and characterize preclinical models of TCL. We identify multiple vulnerabilities that are targetable with currently available agents (e.g., inhibitors of JAK2 or IKZF1) and demonstrate proof-of-principle for biomarker-driven therapies using pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 69 publications
5
72
0
Order By: Relevance
“…39,53 In the presence of IL-2, cS5A hi mice-derived CTL cells were treated with increasing concentrations of these JAK and STAT5 inhibitors, leading to decreased STAT5 activation and cell viability ( Figure 7C Figure S7D). When we used Ruxolitinib we found that Mac1-and Mac2A cells that harbor a JAK2-translocation were sensitive 54 . Control cell lines were only affected 17 / 28 at significantly higher concentrations (AC-3-19: <20 µM, Online Supplementary Figure S7D, summary on mutations in human cells in Online Supplementary Table S7).…”
Section: Proliferation Of Ptcl Cells Is Highly Sensitive To Targetedmentioning
confidence: 98%
See 1 more Smart Citation
“…39,53 In the presence of IL-2, cS5A hi mice-derived CTL cells were treated with increasing concentrations of these JAK and STAT5 inhibitors, leading to decreased STAT5 activation and cell viability ( Figure 7C Figure S7D). When we used Ruxolitinib we found that Mac1-and Mac2A cells that harbor a JAK2-translocation were sensitive 54 . Control cell lines were only affected 17 / 28 at significantly higher concentrations (AC-3-19: <20 µM, Online Supplementary Figure S7D, summary on mutations in human cells in Online Supplementary Table S7).…”
Section: Proliferation Of Ptcl Cells Is Highly Sensitive To Targetedmentioning
confidence: 98%
“…In CTCL, overexpression of oncogenic miR-155, 49 54,70 , and ATLL 71 revealed reduced proliferation and immunomodulatory effects on the PTCL tumor microenvironment. 3 Moreover, a small molecule inhibitor of STAT5 SH 2 domain-phosphopeptide interactions 39 resulted in strongly reduced viability in PTCL lines with high STAT5 activity and its successor compound showed significant effects in AML.…”
Section: Proliferation Of Ptcl Cells Is Highly Sensitive To Targetedmentioning
confidence: 99%
“…These findings support the notion that the serial transplantation of PDX models may enhance drug sensitivity, which in turn may contribute to the observations of variable clinical responses. Because of proven discrepancies in drug sensitivity in later passage PDXs, subsequent studies have modified the experimental design to use early passage PDX models . A recent study in head and neck squamous cell carcinoma showed genomic SMAD family member 4 (SMAD4) alterations in PDX .…”
Section: Aggressive Phenotypes and Variable Drug Sensitivitymentioning
confidence: 99%
“…In this context, patientderived xenograft models using human AITL cell lines with defined causative mutations may provide further insights. 56,57 In summary, our data suggest that ongoing T-B-cell cross talk is a driving force for the progression of Tfh-derived T-cell lymphomas. Importantly, this may apply not only to AITL but also to other peripheral T-cell lymphomas with features of Tfh origin.…”
Section: Discussionmentioning
confidence: 72%